Evaluation of business strategy of song da 4 joint stock company = Đánh giá chiến lược kinh doanh của Công ty Cổ phần Sông Đà 4 - Nguyễn, Tiến Dũng (2020)
Aims of the studyBased the theoretical issues, the fundamentalsof business strategy, how to set up and evaluate a business strategy, the author analyzes and evaluates the existingstrategies of Song Da 4 Joint Stock Company. After that, the author analyzes the changes of the internal and external environment to see the nonconformity of the existingstrategy. Thereby, the author proposes a number of solutions to improvethe strategy of Song Da 4 Joint Stock Company